2016
DOI: 10.1055/s-0042-107251
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Metabolic and Perceptual Response during Sprint Training

Abstract: This study aimed to analyze perceptual, metabolic and mechanical responses to sprint training sessions. 9 male high-level sprinters performed 40 m running sprints up to a loss of 3% in speed, with 4 min rests between sets. Perceptual (rating of perceived exertion, RPE), mechanical (speed and countermovement jump height loss) and metabolic (blood lactate and ammonia) parameters were measured pre-exercise and after each sprint was performed. Relationships between the variables were calculated with a 90% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…1c). CMJ height has turned out to be a useful and simple tool for monitoring and quantifying neuromuscular fatigue induced by the sprint training session [15,16]. In our study, CMJ height (expressed as %CMJ max ) showed a strong relationship with blood lactate concentration (r = − 0.83) (▶ Fig.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…1c). CMJ height has turned out to be a useful and simple tool for monitoring and quantifying neuromuscular fatigue induced by the sprint training session [15,16]. In our study, CMJ height (expressed as %CMJ max ) showed a strong relationship with blood lactate concentration (r = − 0.83) (▶ Fig.…”
Section: Discussionmentioning
confidence: 62%
“…This relationship suggests that the athletes with the lowest %CMJ max values, which means the highest loss of CMJ height, tended to be those with the highest blood lactate concentration and, therefore, with the highest anaerobic glycolysis activation. Previous studies have also shown strong correlations between the CMJ height loss and the metabolic responses such as lactate and ammonia in sprinters (r = 0.95 and r = 0.96, respectively) [15] and in 400-m runners (R 2 = 0.68 and R 2 = 0.51, respectively) [20]. Gorostiaga et al [20] suggested that for blood lactate levels not exceeding 8-12 mmol • L − 1 , the jumping height did not change significantly from maximum values; however, when blood lactate concentrations came to exceed approximately 8-12 mmol • L − 1 , the jumping height decreased sharply.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…However, the physiological impact associated with acute fatigue and recovery using different modified SIT protocols has not been described. In this respect, practical and simple evaluation tools such as HR recovery (HRR), HR variability (HRV) (Stanley, Peake, & Buchheit, 2013), and vertical jump performance (Jimenez-Reyes, et al, 2016;Morcillo, et al, 2015) could be useful for identifying differences in acute fatigue between SIT protocols. This information could be important for designing complex training sessions in which strength exercises are performed after endurance efforts (Fyfe, Bartlett, Hanson, Stepto, & Bishop, 2016).…”
Section: Introductionmentioning
confidence: 99%